Examining heterotypic continuity of psychopathology: a prospective national study. Issue 12 (12th April 2017) - Blanco, C.; Wall, M. M.; Wang, S.; Olfson, M.
Abstract : Background: Individuals with one psychiatric disorder are at increased risk for incidence and recurrence of other disorders. We characterize whether the magnitude of such heterotypic continuity varies based on whether the first disorder remits or persists over time. Method: Cohorts were selected from participants in the National Epidemiologic Survey on Alcohol and Related Conditions wave 1 (2001–2002) and wave 2 (2004–2005) surveys with ⩾1 mood, anxiety, or substance use disorder at wave 1. Among respondents remitting ( n = 6719) or not remitting ( n = 3435) from ⩾1 of disorder at wave 2, the analyses compared the odds of developing new disorders. Results: As compared with adults whose disorders persisted from wave 1 to wave 2, those with ⩾1 remission had lower odds of incidence or recurrence of another disorder. Remission from alcohol dependence [odds ratio (OR) 0.4, 95% confidence interval (CI) 0.3–0.5] and drug dependence (OR 0.4, 95% CI 0.3–0.6) were associated with the lowest odds of incidence of another disorder. Social anxiety disorder was associated with the lowest adjusted odds of recurrence (adjusted OR = 0.2, 95% CI 0.1–0.6). Remission of disorders within one class (mood, anxiety, substance use) was consistently associated with lower odds of incidence or recurrence of disorders from the same class than with developing disorders from the other classes. Conclusions: Remission from common psychiatric disorders tends to decrease the risk for incidence or recurrence of disorders and this effect is stronger within than across disorder classes. These results do not support the concept of heterotypic continuity as a substitution of one disorder for another.